Leadership Contribution of Changing School Principals and School Climate Towards the Utilization of the Independent Teaching Platform - Susi Hendriani; Yahya; Rifma; Jasrial (Postgraduate, University of Mataram, 2024)
To improve the maximum use of the free learning platform by teachers, it is necessary to explore in more depth the problems that influence it, what factors influence it, and prevent the use of the free learning platform by teachers from being carried out as it should. Research aims to determine the correlation between the principal's change in leadership and the school climate in West Pasaman Regency State High School, the change in leadership of the school principal contributes to the use of the independent teaching platform, The school climate contributes to the use of the teacher's use of the freedom to teach platform, The principal's change leadership and the school climate contribute together to the use independent platform for teaching, This research uses a correlational quantitative method with an